Media Hydraulics Govern Pakchoi (Brassica chinensis) Growth under Floating Sub-irrigation - Hilda Agustina; Lily Endah Diansari; K.H. Iskandar (Program Studi Teknik Pertanian Universitas Hasanuddin, 2026)
Floating vegetable cultivation can reduce production constraints in wetland areas, but its performance depends on the capacity of planting and suction media to regulate capillary water supply in the root zone. This study evaluated the effects of media hydraulics on root-zone moisture, growth, and yield of pakchoi under a floating sub-irrigation system. A greenhouse experiment was arranged using two planting media, namely soil:rice husk charcoal:manure (1:1:1) and soil:manure (3:1), combined with two suction media, namely crushed tile particles and fabric wick, with three replications. Hydraulic conductivity, bulk density, root-zone moisture dynamics, plant height, leaf number, and fresh biomass were observed. The soil:manure medium had lower hydraulic conductivity (4.23 × 10⁻⁵ cm s⁻¹) and higher bulk density (0.97 g cm⁻³), indicating greater water retention capacity than the more porous medium. The combination of soil:manure and crushed tile suction media produced the best crop response, with plant height of 22.17 cm, 10 leaves plant⁻¹, and fresh biomass of 86.21 g plant⁻¹. These results indicate that floating sub-irrigation performance is governed by the balance between capillary water supply and root-zone moisture retention. The system can be developed as a passive, low-energy irrigation technology for wetland vegetable cultivation.